Mixed Finite Element Methods for a Strongly Nonlinear Parabolic Problem (Journal of Computational Mathematics, 1999)
A mixed finite element method is developed to approximate the solution of a strongly nonlinear second-order parabolic problem. The existence and uniqueness of the approximation are demonstrated and $L^2$-error estimates are established for both the scalar function and the flux. Results are given for the continuous-time case. \u00a0
Keywords: Finite element method; Nonlinear parabolic problem.